Effect of Adding Stevia Sweetener (Stevia rebaudianna) and Arabic Gum Filler on the Physicochemical Properties of Chayote Squash (Sechium edule) Powder Drink - Nuraziz, Chofifah Endar; Khairi, Amalya Nurul (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Chayote squash (Sechium edule) is renowned for high potassium (125 mg), fiber (1.7 g), and antioxidant compounds including flavonoid, polyphenol, tannin, and saponin. The plant has the potential to be processed into powder drink with the addition of stevia powder and arabic gum . Stevia provides 200 – 300 times the sweetness of sucrose and non-calorie, while arabic gum is used as a bulking agent to improve the physical character of powder drink. Therefore, this study aimed to determine the physicochemical properties of chayote squash powder drink with variations of stevia powder and arabic gum. The method used was a two factorial complete randomized design with variations in stevia powder of 2% and 4% as well as arabic gum of 10% and 15%. Each treatment was repeated three times and powder drink was processed using foam mat drying method at 70 °C for 6 hours. The parameters observed include yield, water holding capacity (WHC), solubility, hardness, springiness, water content, ash content, pH, total dissolved solids (TDS), and antioxidant activity, while the data were analyzed using Two-way ANOVA without interaction. The results showed that the addition of stevia powder and arabic gum significantly affected yield, WHC, water content, pH, TDS, and antioxidant activity. However, no significant effect was observed on solubility, hardness, springiness, and ash content. The best formulation was found to be S2A2 containing 4% stevia powder + 15% arabic gum, with 9.69% yield, 37.65% solubility, WHC 37.44%, hardness 257.61 N, springiness 0.683, moisture content 5.02%, ash content 5.43%, pH 5.73, TDS 5.7 °Brix, and antioxidant activity of 143.00 ppm.